Documenting catastrophic spending on health by migrant slum population - Mehnaz, Saira; Abedi, Ali Jafar; Fazli, Shazia Farooq; Mushfiq, Sakeena; Khan, Zulfia; Ansari, M Athar (Indian Journal of Community Health, 2019)
Background: India ranks among the bottom five countries in public health spending. Out of pocket spending of households on healthcare is almost 70% of income and reimbursement in any form availed by households whose members are employed in the formal sector is negligible. Objectives: To determine the usual source of medical care opted for by the study population. To find out the illness pattern and its age/sex distribution in the study population. To find out the expenditure incurred on illness and its source of procurement by the study population. Methodology: 52.42% urban Aligarh resides in slums. A cross sectional study was done to study the newer slum pockets. 3409 households with a population of 16,978 were studied with the help of pretested questionnaire; SPSS 20 was used for statistical analysis. Results: In our study, we found that almost all the households suffered from catastrophic health expenditure. The study population, which was already vulnerable owing to their low socio-economic and migrant status was further forced into poverty and indebtedness on account of expenditure on illness. Conclusions: National health financing systems should be designed to protect households from financial catastrophe, by reducing out-of-pocket spending.